Prospectives of Coffee Production and Marketing (The Value Chain Approach): The Case of Yirgachefe District, Gedeo Zone, Southern Nation Nationalities and Peoples Regional State, Ethiopia (Global Journal of Science Frontier Research, 2019)
Coffee produced in Yirgachefe is internationally known as the rarest and most prized coffee, especially in America. But farmers in Yirgacheffe district complain that they are not benefited from the existing coffee supply, and half of the coffee supplied to Ethiopian Commodity Exchange(ECX) to be exported does not fulfill the quality criteria of ECX. These might be due to some technical and socio-economic factors. Thus this study was conducted to identify those determinants reducing the quality of Yirgachefe coffee. The general objective of this study was analyzing coffee value chain and Its specifics were to trace the value chain of Yirgachefee coffee AS-IS from input supply to consumption, to identify all the constraints that impede the competitiveness of coffee produced in Yirgachefe in the national & global market and to determine the role of actors in the coffee value chain for the intervention.
Keywords: coffee producers; coffee value chain; ecx; coffee processing industries